Role of brain natriuretic peptide (BNP) in risk stratification of adult syncope. Issue 11 (22nd October 2007) - Reed, Matthew J; Newby, David E; Coull, Andrew J; Jacques, Keith G; Prescott, Robin J; Gray, Alasdair J
Abstract : Aims: To assess the value of a near-patient brain natriuretic peptide (BNP) test to predict medium term (3 month) serious outcome for adult syncope patients presenting to a UK emergency department (ED). Methods: This was a prospective cohort pilot study. Consecutive patients aged ⩾16 years presenting with syncope over a 3 month period were eligible for prospective enrolment. All patients who were medium or high risk according to our ED's existing syncope guidelines underwent near-patient BNP testing using the Triage point of care machine. Results: 99 patients were recruited. 72 of 82 high and medium risk patients underwent BNP measurement. 11 patients had a serious outcome, 9 of whom had BNP measured. In 25 (35%) patients, BNP was ⩾100 pg/ml, and in 3 of these it was >1000 pg/ml. 6 of the 25 patients (24%) with a BNP >100 pg/ml, and all 3 patients with a BNP >1000 pg/ml, were in the serious outcome group. BNP was raised over 100 pg/ml in 6 of the 9 serious outcome patients having a BNP measured (66%), and over 1000 pg/ml in 3 (33%). Conclusions: This early work suggests that BNP may have a role in the risk assessment of syncope patients in the ED. Further work is required to see how BNP interacts with other clinical variables. Near-patient BNP testing may be shown to be an independent predictor of adverse outcome either alone or incorporated into existing syncope clinical decision rules and scores in order to improve their sensitivity and specificity. Further studies are required to evaluate this.